SISTEM INFORMASI PEMESANAN JASA EVENT ORGANIZER PADA PT. CENTRAL ADVENTURE INDONESIA KABUPATEN BOGOR - Muhammad Rifky; Sunarti Sunarti (Jupiter: Journal of Computer & Information Technology, 2023)
Event Organizer is a system for managing order data, payment data, and payment confirmation which aims to make it easier to provide optimal service to consumers. PT. Central Adventure Indonesia provides event services and event packages, customers come to the office to place an order or just find out information on the services provided. Based on these problems, researchers conducted research to produce an event organizer information system design, starting from the ordering process, and price confirmation, to recording event organizer reports so that it can make it easier for admins to process event data and event booking transactions. The method used in system design is the Waterfall Model. The classic model is systematic, sequential in building software, and easy to use. This research resulted in the design of an information system for ordering web-based event organizer services that can overcome the problems faced by PT. Central Adventure Indonesia is in the process of ordering services and managing reports.